Assessing Work-based Learning in German Dual VET from the Apprentices' Perspective - the Development of an Inventory - Velten, Stefanie [Verfasser]; Schnitzler, Annalisa [Verfasser] (My University, 2019)
"The German system of dual VET is regarded to be a key component in providing the economy with skilled workers needed to ensure economic growth. Being involved in real working processes apprentices should be able to gain action-related skills and competences. Training regulations for each training occupation offer guidelines and regulations what tasks to train and which skills to provide. However, companies differ notably in the properties of the immediate working and training environment they place their apprentices in, i.e. the concrete work tasks and the social climate at the workplace. In addition, the extent to which suitable teaching and learning methods are applied at the workplaces differs. Consequently, it is not sufficient to integrate work-based learning modules in vocational training in the dual system, but they need to be designed so that apprentices benefit from them. To design motivating and skill fostering working environments, the apprentices' perspective and their perceptions on working conditions are crucial. With that in mind, we developed a self-report questionnaire with which apprentices can rate such characteristics of their working environment at the training company. The development and application of the questionnaire were carried out as part of a BIBB research project on competence development and its antecedents in two German training occupations (research project "Aqua.kom"). With the questionnaire, we assessed different aspects of the workplace and training conditions at the training company from the perspective of prospective mechatronics fitters, and related them to apprentices' motivation and self-efficacy with regard to their work at the company." (excerpt; BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; L 6 Qualität; Betriebliche Berufsausbildung; Lernen am Arbeitsplatz; Lernumgebung; Ausbildungsqualität; Auszubildender; Ausbildungszufriedenheit; Fragebogenerhebung